Is muscle and protein loss relevant in long‐term fasting in healthy men? A prospective trial on physiological adaptations. Issue 6 (20th October 2021) - Laurens, Claire; Grundler, Franziska; Damiot, Anthony; Chery, Isabelle; Le Maho, Anne‐Laure; Zahariev, Alexandre; Le Maho, Yvon; Bergouignan, Audrey; Gauquelin‐Koch, Guillemette; Simon, Chantal; Blanc, Stéphane; Wilhelmi de Toledo, Françoise
Abstract: Background: Fasting is attracting an increasing interest as a potential strategy for managing diseases, including metabolic disorders and complementary cancer therapy. Despite concerns of clinicians regarding protein catabolism and muscle loss, evidence‐based clinical data in response to long‐term fasting in healthy humans are scarce. The objective of this study was to measure clinical constants, metabolic, and muscular response in healthy men during and after a 10 day fast combined with a physical activity programme. Methods: Sixteen men (44 ± 14 years; 26.2 ± 0.9 kg/m 2 ) fasted with a supplement of 200–250 kcal/day and up to 3 h daily low‐intensity physical activity according to the peer‐reviewed Buchinger Wilhelmi protocol. Changes in body weight (BW) and composition, basal metabolic rate (BMR), physical activity, muscle strength and function, protein utilization, inflammatory, and metabolic status were assessed during the 10 day fast, the 4 days of food reintroduction, and at 3 month follow‐up. Results: The 10 day fast decreased BW by 7% (−5.9 ± 0.2 kg, P < 0.001) and BMR by 12% ( P < 0.01). Fat mass and lean soft tissues (LST) accounted for about 40% and 60% of weight loss, respectively, −2.3 ± 0.18 kg and −3.53 ± 0.13 kg, P < 0.001. LST loss was explained by the reduction in extracellular water (44%), muscle and liver glycogen and associated water (14%), and metabolic active lean tissue (42%). Plasma 3‐methyl‐histidine increased until Day 5 of fasting and then decreased, suggesting that protein sparing might follow early proteolysis. Daily steps count increased by 60% ( P < 0.001) during the fasting period. Strength was maintained in non‐weight‐bearing muscles and increased in weight‐bearing muscles (+33%, P < 0.001). Glycaemia, insulinemia, blood lipids, and blood pressure dropped during the fast ( P < 0.05 for all), while non‐esterified fatty acids and urinary beta‐hydroxybutyrate increased ( P < 0.01 for both). After a transient reduction, inflammatory cytokines returned to baseline at Day 10 of fasting, and LST were still lower than baseline values (−2.3% and −3.2%, respectively; P < 0.05 for both). Conclusions: A 10 day fast appears safe in healthy humans. Protein loss occurs in early fast but decreases as ketogenesis increases. Fasting combined with physical activity does not negatively impact muscle function. Future studies will need to confirm these first findings.